2004
DOI: 10.1007/s00421-003-1004-2
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary activation and mechanical performance of human triceps surae muscle after exhaustive stretch-shortening cycle jumping exercise

Abstract: The purpose of this study was to examine neuromuscular factors that may contribute to post exercise force loss and subsequent recovery after exhaustive stretch-shortening cycle (SSC) exercise. Six subjects were fatigued on a sledge apparatus by 100 maximal rebound jumps followed by continuous submaximal jumping until complete exhaustion. Exercise-induced changes in neuromuscular performance were followed up to 7 days post exercise. The total number of jumps in the SSC exercise ranged from 336 to 1392. The SSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 30 publications
1
31
0
3
Order By: Relevance
“…The results are also in good agreement with previous studies on adults [38] and, moreover, suggest that the relative contributions of central and peripheral mechanisms do not significantly differ between the groups representing various stages of maturation. Probably neural adjustments, particularly group III and IV afferent inhibition and disfacilitation of spindle support, are more inherent in prolonged running exercise upwards of 30 min [39] or exhaustive jumping exercise [40] than short-term sprinting. From the practical point of view, the results emphasize running speed and aerobic training in children and adolescents as a good basis for the adult phase.…”
Section: Resultsmentioning
confidence: 99%
“…The results are also in good agreement with previous studies on adults [38] and, moreover, suggest that the relative contributions of central and peripheral mechanisms do not significantly differ between the groups representing various stages of maturation. Probably neural adjustments, particularly group III and IV afferent inhibition and disfacilitation of spindle support, are more inherent in prolonged running exercise upwards of 30 min [39] or exhaustive jumping exercise [40] than short-term sprinting. From the practical point of view, the results emphasize running speed and aerobic training in children and adolescents as a good basis for the adult phase.…”
Section: Resultsmentioning
confidence: 99%
“…Other options could be muscle group speciWcity and exercise volume. For example, it has been shown that 1,342 jumps performed on a sledge ergometer induced greater increase in muscle stiVness than 428 jumps, and this may have augmented the spindle sensitivity to stretch (Kuitunen et al 2004). Another possibility is that the sensitivity of the superimposed electrical stimulation technique is increased at greater muscle length because of the increased stiVness of the series elastic component.…”
Section: Voluntary Activationmentioning
confidence: 97%
“…This agrees with the Wndings of Prasartwuth et al (2005) that reduced voluntary activation contributes to force loss after eccentric exercises with the elbow Xexors. Also, muscle activation failure has been found to contribute to the post-exercise force deWcit after stretchshortening cycle exercises (Kuitunen et al 2004;Millet et al 2003). It has been reported that decreased aVerent feedback to the motoneurone pool (Duchateau et al 2002) increased the activity of group III and IV aVerents (Bigland-Ritchie et al 1986), increased recurrent inhibition (Löscher et al 1996) and supraspinal fatigue (Gandevia 2001) can lead to suboptimal activation of the muscles.…”
Section: Voluntary Activationmentioning
confidence: 99%
“…The total number of SSC jumps ranged dramatically between subjects, similar to that reported by Kuitunen et al (2003). The rebound height was set at 80% of the individual maximal rebound performance measured from a series of maximal drop jumps performed from different starting heights during a preliminary testing session.…”
Section: Exp Group Designmentioning
confidence: 98%
“…Supporting the existence and the functional role of a prolonged reduction in stretch-reflex sensitivity, Avela et al (1999) showed a bimodal trend of changes in the tolerance to high ground impacts, and in the active (M1) stretch-reflex EMG response. This hypothesis relies on the prolonged EMG reflex responses measured in passive stretch- (Avela et al 1999;Balestra et al 1991;Kuitunen et al 2003;Nicol et al 1996a and H-reflex (Avela et al 1999;Nicol et al 1996b) testing conditions. Furthermore, most of the passive EMG reflex responses were recorded from the soleus muscle (SOL), whereas the fatiguing SSC exercise involved the overall lowerlimb extensor muscles.…”
Section: Introductionmentioning
confidence: 98%